Pengembangan Sistem Informasi Perpustakaan Menggunkan Sistem Barcode - Rosdiana, Rosdiana; Basri, Muh; Marlina, Marlina; Masnur, Masnur (JURNAL UNITEK, 2025)
Libraries serve a strategic role as information centers that support academic activities in higher education institutions. However, conventional library services often face challenges such as processing delays, recording errors, and limited access to information. This study aims to develop and evaluate a barcode-based library information system to improve service efficiency and quality. A descriptive quantitative approach was employed, with data collected through questionnaires, observations, and documentation. Respondents consisted of 30 students and 30 library staff from Universitas Muhammadiyah Parepare who had used the system. The findings indicate that most respondents were satisfied with the system's ease of access, transaction speed, and user interface design. The barcode-based system effectively reduced manual workloads, accelerated the borrowing and returning process, and enhanced data accuracy. Nonetheless, certain features such as notifications and reporting require further improvement. This study highlights the importance of developing information systems that are adaptive to user needs and grounded in empirical evaluation. The system developed not only meets technical expectations but also contributes significantly to enhancing the quality of academic information services.